Analisis Pengaruh Arus Kas Bebas dan Ukuran Perusahaan Terhadap Manajemen Laba (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - B1031141041, Berry Rizky Noviandy (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
The purpose of this study is to determine the effect of variables, free cash flow and the firms’ size, towards earnings management in manufacturing companies, miscelleneaous manufacturing sub-sectors which listed in Indonesia Stock Exchange. This study use secondary data from purposive sampling technique with an amount of 14 companies for the period of 2014-2016.Technique of data analysis using multiple linear regression analysis and hypothesis test by using t test and f test which firstly done the classic assumption test to know the normality of the data. The use of t test is to know the effect of independent variables towards dependent variables and the f test is used to know the effect of independent variables along with dependent variables.The results of this study indicate that partially, free cash flow has no effect on earnings management and firm size also has no effect on earnings management. Then, free cash flow and the firm size together do not affect the earnings management in the manufacturing companies, miscelleneaous manufacturing sub-sectors that are listed in the Indonesia Stock Exchange.Keywords: Free Cash Flow, Firm Size, Earnings Management